2022
DOI: 10.1186/s13071-022-05279-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular survey of Babesia parasites in Kenya: first detailed report on occurrence of Babesia bovis in cattle

Abstract: Background Among protozoan parasites in the genus Babesia, Babesia bigemina is endemic and widespread in the East African region while the status of the more pathogenic Babesia bovis remains unclear despite the presence of the tick vector, Rhipicephalus microplus, which transmits both species. Recent studies have confirmed the occurrence of R. microplus in coastal Kenya, and although B. bovis DNA has previously been detected in cattle blood in Kenya, no surveillance has been done to establish i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…Blood samples were systematically collected from the coccygeal vein of cows using anticoagulant-treated tubes to prevent clotting. These samples were then promptly transferred to petri dishes for further processing (10,11).…”
Section: Methodsmentioning
confidence: 99%
“…Blood samples were systematically collected from the coccygeal vein of cows using anticoagulant-treated tubes to prevent clotting. These samples were then promptly transferred to petri dishes for further processing (10,11).…”
Section: Methodsmentioning
confidence: 99%
“…The spread and epidemic characteristics of B. bovis are important components in the prevention and control of bovine worm disease caused by this pathogen. Studies have shown that R. microplus ticks are an important biological medium for B. bovis [8,9]. Therefore, based on the prevalence of ticks, the prevalence of B. bovis is seasonal and time-sensitive.…”
Section: Introductionmentioning
confidence: 99%